1992
DOI: 10.1088/0954-0083/4/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides Based on Furfuryl-Disulphide

Abstract: Poly (disulphido-imides) were prepared by Diels-Alder (DA) reaction of furfuryl-disulphide (FDS) with various bismaleimides. The DA reaction was carried out in xylene as solvent, as well as in bulk, followed by aromatization of terrahydrophthalimide intermediates in the presence of acetic anhydride. All the poly (disulphido-imide)s were characterized by elemental analyses, IR spectral data and thermogravimetry. The poly (disulphido-imide)s exhibit moderate thermal stability. Preliminary test for glass reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Other polyimides are mostly made from condensation of tetracarboxylic acid and diamines and are more thermally stable than polyimides made from bismaleimides. It is also noted that the produced poly(ether-imide)s have better thermal stability then those reported earlier by the present authors [1][2][3][4][5][6]. Because of the non-processability of the present insoluble poly(ether-imide), a novel approach was also conducted to develop a matrix system for poly(ether-imide)-glass-fiber composites.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Other polyimides are mostly made from condensation of tetracarboxylic acid and diamines and are more thermally stable than polyimides made from bismaleimides. It is also noted that the produced poly(ether-imide)s have better thermal stability then those reported earlier by the present authors [1][2][3][4][5][6]. Because of the non-processability of the present insoluble poly(ether-imide), a novel approach was also conducted to develop a matrix system for poly(ether-imide)-glass-fiber composites.…”
Section: Resultsmentioning
confidence: 53%
“…One of the authors (HSP) and his co-workers have reported the preparation of polyimides through Diels-Alder (DA) reaction of bisfuran derivatives=furan resins and bismaleimides [1][2][3][4][5][6]. The reports indicate that thermally stable polyimides can be created in situ at lower temperature than conventional polyimide [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the approaches to get the polyimides via Diels-Alder (DA) reaction of dienes and bismaleimides [2,3] . One of the authors (HSP) has established such type of polyimides via DA reaction from agricultural waste products such as furan derivatives [4][5][6][7][8][9][10] . He established the different types of polyimides like poly(ether-imide), poly(sulfone-imide), poly(urethaneimide), poly(s-triazine-imide)s and poly(amido-imide) through Diels-Alder polymerization of bisfurans and bis (maleimide)s with wide structural variation.…”
Section: Introductionmentioning
confidence: 99%
“…He established the different types of polyimides like poly(ether-imide), poly(sulfone-imide), poly(urethaneimide), poly(s-triazine-imide)s and poly(amido-imide) through Diels-Alder polymerization of bisfurans and bis (maleimide)s with wide structural variation. The key focus of these polyimides [4][5][6][7][8][9][10][11][12][13][14][15][16] is that they have low temperature processing with good thermal stability in air. Most of the bismaleimides are based on simple diamines and other structural modification [17] .…”
Section: Introductionmentioning
confidence: 99%